ULTIMATE FRISBEE AS A POTENTIAL TEAM SPORTS FOR PHYSICAL EDUCATION IN COLLEGES AND UNIVERSITIES - Tianio, Jomar S.; Jefferson M. De Castro, Mat; Charlie D. Sabinay, Mat; Francis R. Gura, Mat (International Journal of Multidisciplinary Research and Studies, 2023)
Ultimate Frisbee is a team sport that is now gaining popularity around the world. It is a non-contact, self-refereed sport using one disc (Frisbee). It is played between two teams of 7 players (sometimes 5), on a rectangular pitch with endzones at either end. At our tertiary level, the subject of physical education is a part of the curriculum of all courses. The physical education programs the usual sports played by Filipinos include basketball, volleyball, badminton, swimming, and indigenous sports. However, can Frisbee as a sport that slowly gains fame in the Philippines that doesn’t require any physical contact with many players be accepted by college students and other people engaged in the academe and have encountered ultimate frisbee as a potential team sport for Physical Education. An additional option of team sports to be played in the college level may improve their interest and participation. The researcher would like to know the perception of different individuals who are involved in the academe and those who are involved in ultimate Frisbee by gathering data using a validated questionnaire. It was shown on the different scales of data that Ultimate Frisbee gained a positive result. It can be drawn from the results after the statistical treatment that the sport Ultimate Frisbee can be taught as a team sport in colleges and universities. The researcher’s output is a validated training module that teachers would be using as a guide in teaching Ultimate Frisbee.